Pengaruh Perencanaan Anggaran, Pelaksanaan Anggaran dan Evaluasi Anggaran terhadap Penyerapan Anggaran pada Pemerintah Kota Bekasi - Karina Wijayanti; Yulianto (Neraca : Jurnal Akuntansi Terapan, 2025)
Optimizing budget absorption is very important to ensure the effectiveness and efficiency of budget use in governance. This study aims to analyze the effect of budget planning, budget execution, and budget evaluation on budget absorption in the Bekasi City Government. The method used in this research is quantitative with a survey approach. Data were obtained through distributing questionnaires to 240 technical implementing officials of activities in the Bekasi City Government selected using simple random sampling technique. The results showed that budget planning had a positive and significant effect on budget absorption by 38.4%. Budget implementation also has a positive and significant effect on budget absorption by 61.14%. Meanwhile, budget evaluation has no positive and significant effect on budget absorption with a coefficient of determination (R square) of 8.6%. However, simultaneously, budget planning, budget execution, and budget evaluation have a positive and significant influence on budget absorption by 62.9%, indicating that most of the variation in budget absorption can be explained by these three variables. However, the remaining 37.1% is influenced by other factors not examined in this study.